Creditor Rights, Enforcement, and Debt Ownership Structure: Evidence from the Global Syndicated Loan Market - Esty, Benjamin C.; Megginson, William L. (Journal of Financial and Quantitative Analysis, 2003)
Benjamin C. Esty, William L. Megginson, Creditor Rights, Enforcement, and Debt Ownership Structure: Evidence from the Global Syndicated Loan Market, The Journal of Financial and Quantitative Analysis, Vol. 38, No. 1 (Mar., 2003), pp. 37-59